Strengthening Legal Accountability in Regional Budgeting: A New Framework for Indonesia - Suhartono, Slamet; Sartono, S.; Hadi, Syofyan; Fahmi, F. (Journal of Ecohumanism, 2025)
Delays in regional budget approvals remain a persistent issue in Indonesia, disrupting governance and public service delivery. This study proposes a novel framework for strengthening legal accountability in the budgeting process by enhancing regulatory enforcement and institutional oversight. Using a doctrinal legal research method complemented by qualitative analysis, this paper examines the weaknesses of existing sanctions under Law No. 23 of 2014 and identifies best practices from international governance systems. The findings suggest that a comprehensive reform of administrative sanctions, coupled with technological innovations and stakeholder collaboration, can significantly improve fiscal discipline. The study provides policy recommendations to reduce budgetary inefficiencies and foster transparent, accountable governance. This research contributes to the broader discussion on fiscal governance and highlights the necessity of integrating legal frameworks with technological advancements to ensure compliance.